Yves Couder: Putting mechanics back into the shoot apical meristem - Traas, Jan; Hamant, Olivier (Comptes Rendus. Mécanique, 2020)
In 2008, we published an article proposing that the microtubular cytoskeleton in plants use maximal tensile stress directions to guide organ growth []. Yves Couder was instrumental in that project. Here are some memories and prospects from this collaborative and interdisciplinary endeavor.